Pedagogies for Later-Life Music Learning and Participation Facilitating Creative Musical Development in Later-Life - Creech, Andrea; Enright, Colin; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This open access book presents evidence-based participant and facilitator perspectives on later-life music learning and participation. The chapters explore the principles and practices that can facilitate and support meaningful music-making in a range of non-formal later-life contexts, highlighting consistent as well as context-specific pedagogical issues. Case study examples are used to examine issues relating to pedagogy as improvisation, the use of technology to support creativity and meaningful music experience, facilitation of the use of music for creativity, sense of belonging, musical identities and musical development in later-life, and more. The book concludes with an innovative and creative pedagogical model to support critical reflection on values, frameworks, and practices in later-life music learning and participation. The book will be accessible and relevant for music researchers and educators, music education students and community music leaders alike. Andrea Creech is Professor of Music Pedagogy at the Schulich School of Music, McGill University, Canada. Andrea$1 (Bs research has covered a wide range of issues in formal and informal music education contexts, including interpersonal dynamics in instrumental learning, informal learning, inclusion, lifelong learning and active ageing with music, and music for positive youth development. Colin Enright is a music educator, conductor, and PhD candidate in Music Education at McGill University, Canada. Colin$1 (Bs research is focused on group music in community and educational settings and its effects on mental health, resilience, and general wellbeing.s
Chapter 1. Pedagogies for music learning and participation in later-life: Setting the scene(Andrea Creech) -- Chapter 2. Relational pedagogies for later-life learning as participation(Isabelle Cossette and Andrea Creech) -- Chapter 3. Building community within online later-life creative community music(Colin Enright, Andrea Creech, Lisa Lorenzino and Mariane Generale) -- Chapter 4. Embracing the unexpected: Improvisational pedagogy for collaborative music-making in a care home setting (Richard Barham, Aaron Liu-Rosenbaum,Graylen Howard and Andrea Creech) -- Chapter 5. Later-life creative musical experience: Pedagogies for creativity in lifelong music learning and participation (Andrea Creech, Aaron Liu-Rosenbaum and David Fortier) -- Chapter 6. The Circle of Music Choir for those living with dementia , their partner caregivers, and teen volunteers: Incorporating technology as necessity (Sasha Judelson and Lee Willingham) -- Chapter 7. Popular music as a resource for exploring later-life identities in music (Aaron Liu-Rosenbaum and Andrea Creech) -- Chapter 8. Facilitating later-life community music learning in offline and online contexts (Angelina Lynne, Malinalli Peral Garcia and Andrea Creech) -- Chapter 9. Adapting to change: A community band$1 (Bs journey in using technology to continue music-making during the pandemic (Mariane Generale, Audrey-Kristel Barbeau and Andrea Creech) -- Chapter 10. Pedagogies for later-life music learning and participation: critical reflections (Andrea Creech and Colin Enright).s
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Continuing education; Music; Gerontology; Teaching; Art -- Study and teaching; Lifelong Learning; Music; Gerontology; Pedagogy; Creativity and Arts Education